ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH TABUNGAN HAJI BJB SYARIAH KCP BOGOR JEMBATAN MERAH - Salsabila, Verlya; Thantawi, Tubagus Rifqy; Anwar, Miftakhul (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This study is motivated by many of the same products all banks compete in finding customers. For this reason, they must have the right strategy to attract customers interest in using hajj savings products. This study aims to identify and analyze the factors that influence people’s decisions to become BJB Syariah Bank customers. The type of research used in this thesis is a quantitative method. The data that is processed is in the form of partial data and simultaneous data. Data analysis techniques used in this study using observation and questionnaires, data processing using SPSS. From the test results in this study that the most significant cultural, social, personal, and psychological factors in influencing customer decisions in Hajj savings are cultural factors. This can be seen from the coefficient value of 0.281 with a significant value of 0.06. Thus, cultural factors are the most important factors in influencing customer decisions on Hajj savings, when compared to social, personal, and psychological factors.